Creating a student-centred online learning environment for report writing in the sciences and engineering : final report. - Drury, Helen; Jones, Janet (Australian Learning and Teaching Council, 2009)
Report of a project to develop, implement and disseminate an online learning environment, the WRiSE site, to improve student writing in discipline areas where students are known to struggle with their writing. The project focused on undergraduate students in engineering and science. The key deliverables are the two main spaces on the site for each discipline area: help with report writing; and help with understanding content. The report writing area contains interactive explanations, example reports and exercises on the structure and language of each section of a typical report in the discipline. The content area contains exercises on the content of a particular report students are writing or general concepts in the discipline. The website delivered several outcomes: improved understanding and confidence in report writing; and improved understanding and confidence in understanding discipline content related to report writing and improved report writing performance. The website design has allowed students to access modules across the disciplines they are studying in, enhancing their awareness of how knowledge is communicated in different disciplines. [Executive summary, ed]